2011
DOI: 10.1002/bem.20656
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of germination, growth, and photosynthesis in soybean by pre‐treatment of seeds with magnetic field

Abstract: Experiments were conducted to study the effect of static magnetic fields on the seeds of soybean (Glycine max (L.) Merr. var: JS-335) by exposing the seeds to different magnetic field strengths from 0 to 300 mT in steps of 50 mT for 30, 60, and 90 min. Treatment with magnetic fields improved germination-related parameters like water uptake, speed of germination, seedling length, fresh weight, dry weight and vigor indices of soybean seeds under laboratory conditions. Improvement over untreated control was 5-42%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
1
7

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(136 citation statements)
references
References 23 publications
5
106
1
7
Order By: Relevance
“…Area of leaves was taken by pressing the blotted dry leaf on a graph paper (mm) and tracing the exact outline. The area was measured by weighing the graph cuttings of leaves (Shine et al 2011). The mean of five leaves was taken as the average value.…”
Section: Growth Parametersmentioning
confidence: 99%
“…Area of leaves was taken by pressing the blotted dry leaf on a graph paper (mm) and tracing the exact outline. The area was measured by weighing the graph cuttings of leaves (Shine et al 2011). The mean of five leaves was taken as the average value.…”
Section: Growth Parametersmentioning
confidence: 99%
“…Florez et al (2007) observed an stimulation on the growth of maize seeds exposed to 125 and 250 mT stationary magnetic field. Shine et al (2011) found that exposure to magnetic fields improved parameters like water uptake, leaf photosynthetic efficiency and leaf protein content. Although the mechanisms at work in plants and other living systems exposed to a magnetic field are still not well known, several theories have been proposed, including biochemical changes or altered enzyme activities (Phirke et al, 1996).…”
Section: Introductionmentioning
confidence: 97%
“…The magnetic field with intensity of 150 and 200 mT and duration of exposure of one hour stimulates the formation of reactive oxygen in cells of soybean [Shine et al 2012]. Increased level of active forms of oxygen leads to the increase of antioxidant system activity which is the early response of the plants under the stress factor effect [Barаn 1998, Sahebjamei et al 2007, Shine et al 2011]. This mechanism is the basic of the plants adaptations to the external factors [Mamenko et al 2014].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field can cause genes disruption, structural changes of the protein molecules and enzymes that have a negative effect on antioxidant system of the cells [Barаn et al1998, Shine et al 2011.…”
Section: Introductionmentioning
confidence: 99%